2010
DOI: 10.1016/j.bcp.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 inhibits natural killer and γδ T cell cytotoxicity triggered by NKR and TCR through a cAMP-mediated PKA type I-dependent signaling

Abstract: inhibits Natural Killer and γδ T cell cytotoxicity triggered by NKR and TCR through a cAMPmediated PKA type I-dependent signaling. Biochemical Pharmacology, Elsevier, 2010, 80 (6) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 46 publications
2
86
1
1
Order By: Relevance
“…37 Martinet and co-workers reported that PGE2 inhibits TCR-activated gd T cell-cytotoxicity by a cAMP-mediated protein kinase A type I-dependent signaling. 26 In addition, EP2-and EP4-specific agonists reduced intracellular IFNg production in activated gd T cells comparable to the addition of exogenous PGE2. 9 An enhanced release of IFNg often leads to reduced intracellular stores of IFNg.…”
Section: E988460-6mentioning
confidence: 92%
See 2 more Smart Citations
“…37 Martinet and co-workers reported that PGE2 inhibits TCR-activated gd T cell-cytotoxicity by a cAMP-mediated protein kinase A type I-dependent signaling. 26 In addition, EP2-and EP4-specific agonists reduced intracellular IFNg production in activated gd T cells comparable to the addition of exogenous PGE2. 9 An enhanced release of IFNg often leads to reduced intracellular stores of IFNg.…”
Section: E988460-6mentioning
confidence: 92%
“…Similar to the report of Martinet and colleagues, who demonstrated an inhibitory effect of PGE2 on gd T-cell cytotoxicity, we observed that the addition of PGE2 to PDAC cells releasing scarce native PGE2, such as Panc89 and PancTu-I cells, robustly inhibited gd T cell-mediated lysis. 26 In contrast, the addition of exogenous PGE2 to PDAC cells that already released high concentrations of native PGE2 only slightly modulated gd T-cell cytotoxicity, suggesting that the endogenous release of PGE2 by Colo357 cells is sufficient to potently inhibit gd T-cell cytotoxicity. This hypothesis was confirmed by the experiment with the inhibitors Indomethacin and DuP697 that partially abrogated the resistance of Colo357 against gd T-cell mediated lysis.…”
Section: E988460-6mentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, to our knowledge, this is the first report demonstrating the presence in ovarian cancer-associated ascites of PGE2, which has recently been proposed as a strong inhibitor of Vc9Vd2 T-cell cytotoxicity, in ascitic supernatant. 28 The concentration of PGE2 ranged from 0.03 to 35 ng/ml, and the mean concentration was 10.2 6 15.5 ng/ml (Fig. 4a).…”
Section: Pge2 Is a Primary Contributor To The Immunosuppressive Effecmentioning
confidence: 95%
“…Indeed, studies have shown that ovarian ascites contain well-known immunosuppressive factors, including IL-6, IL-10, TGF-b and VEGF. 26,27 Moreover, recently, Fournie et al 28 have demonstrated that PGE2 inhibits the natural Vc9Vd2 T-cell cytotoxicity triggered by the NKR and TCR through cAMP-mediated PKA Type I-dependent signaling.…”
mentioning
confidence: 99%